Asupan Karbohidrat, Asupan Lemak dan PaCo2 pada Pasien Kritis - Dyah Ayu Purwaningrum (Poltekkes Kemenkes Semarang, 2014)
Background:The physiological changes occur deteriorating rapidly on critical patients so that it can lead to death if not quickly and accuratelytreated. Two circumstances that can lead to worsening an organ are hypoxemia and malnutrition. Problems can arise when nutrition administered with inappropriate total energy, such as the provision of excessively carbohydrates cause hipercapnea, hyperglycemia, increased O2 consumption and CO2 production, while low fat intake causes hypoxemia. This research aimed to determine the relationship between carbohydrate and fat intake with changes in PaCO2.Objective : The purpose of this study was to determine the relationship between the intake of carbohydrates and fats with PaCO2 changes in critically ill patients .Method: This researchis observational with cross-sectional researchdesign. The experiment was conducted in the ICU room of Semarang Regional Hospital. Samplesare all subjects who were treated in the ICU room and meet the criteria of inclusion and exclusionand limited in period of 3 weeks. The research subjects were adult age group at least 18 years old male or female with the inclusion criteria of having experienced respiratory failure, using ventilator, not experience shock in the last 24 hours, blood pressure is not hypotension, receiving food through enteral or combination of enteral or parenteral. Its exclusion criteria is patients with complex organ failure clinically diagnostic in 24 hours experienced shock, not fed for≥ 4 hours, with hemoglobin level 8 g/ dL, malnutrition status based on anthropometric TSFexamination. The collected data were age, hemoglobin, blood pressure, TSF, carbohydrate intake, fat intake, changes in PaCO2. Analysis data used Shapiro-Wilk, Pear son Product Moment correlation.Results: The most of carbohydrate intake including in the high category (66.7 %), the majority of fat intake fall in the category of less (58.7 %). The majority of PaCO2 in day 1 and 2 (66.7 % and 50 %) are included in the high category. There was relationship between carbohydrate intake with changes in PaCO2 (p =0,024 r = 0,643). There was relationship between fat intake with changes in PaCO2 (p = 0,046, r = - 0,584).Conclusion: There was relationship between carbohydrate intakes with changes in PaCO2 and there was relationship between fat intake with changes in PaCO2.